Modified three port laparoscopic cholecystectomy versus conventional four port technique - Resutra, Ritvik; Gupta, Rajive; Gupta, Madhu (International Journal of Research in Medical Sciences, 2020)
Background: The current study was undertaken to compare the results of modified three-port laparoscopic cholecystectomy and conventional three or four-port surgery in terms of technical feasibility, safety of the technique, postoperative pain and need of post-operative analgesia, cosmetic satisfaction of the patient and cost effectiveness and were found to be better with the modified technique. Methods: In modified three port laparoscopic cholecystectomy technique, first 10 mm umbilical, second 5 mm epigastric and third 5 mm subcostal ports are made, i.e., "10-5-5" instead of "10-10-5" or "10-10-5-5" of conventional three or four port techniques and finally, gallbladder is extracted through the umbilical port. Results: The pain in the postoperative period and the requirement of postoperative analgesia were significantly less and there was better cosmetic satisfaction of the patients operated by the modified three port laparoscopic cholecystectomy technique as compared to conventional three or four port surgery. Conclusions: The modified three-port laparoscopic cholecystectomy technique is safe and has the same comfort and feasibility to the surgeon along with added advantage of less pain and better cosmetic appearance to the patient in comparison to the conventional three or four-port surgery, with no obvious increase in complications and is definitely a viable alternative procedure for the management of cholelithiasis.